IMPLEMENTASI MOBILE LEARNING DENGAN MODEL ADVANCE ORGANIZER DALAM MENINGKATKAN KEMAMPUAN KOGNITIF KIMIA MAHASISWA - salim efendi; Ricard Fredrik Marpaung (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2018)
The use of internet-based information technology on computers in the information network that is learned through cellular technology, cellular-based applications is easier to use the material provided by lecturers, the presence of mobile learning technology becomes a liaison between students and lecturers in learning, with mobile technology becoming a new alternative in providing learning content / items that are more innovative and dynamic. This study uses qualitative data relating to the questionnaire by looking at the feasibility of mobile learning media that contains relevant indicators on the National Education Standards Agency and quantitative data to determine the results of the effectiveness of mobile learning with advanced organizer models in improving chemical cognitive abilities. this is all study program pharmacy Efarina university students. Data collection is done by objective tests for student learning outcomes. Data were analyzed using SPSS 17.0 with a significant level of 0.05. The results of the study are in the form of mean validation to determine whether or not the media of mobile learning is feasible. The results obtained: (1) The composition of the material / media framework on mobile learning media is feasible and in accordance with the Curriculum (2) Mobile learning media developed for the pharmacy study program in the first semester class is feasible to use the results of standardization 3.58, standardization of language feasibility 3.66, standardization of presentation feasibility of 3.72, graphic standardization of 3.69 (3) is certainly the result that is significant improvement in cognitive abilities of students with the implementation of mobile learning with advance organizer models (Sig.1-tailed <α (0.0285 <0.05)).